1998
DOI: 10.1507/endocrj.45.659
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Role of N-linked Oligosaccharides in Rat Placental Lactogen Action by Site-Directed Mutagenesis.

Abstract: Abstract. To evaluate the role of N-linked oligosaccharides in the molecular action of rat placental lactogen (PL), recombinant PL-Im (recPL-Im) and three recPL-Im mutants were produced in COS-7 cells. The mutants, carrying Gin substitutions of Asn at putative N glycosylation sites, were generated via sitedirected mutagenesis, i.e. two single mutants (N79Q, N128Q) and one double mutant (N79Q/N128Q). Western blot analysis revealed that wild type recPL-Im had a molecular mass of 34 kDa , which was reduced to 29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…1 and 2). These data are consistent with our earlier study in which PL-I showed higher proliferating activity than PRL (4).…”
Section: Induction Of Pal31 Expression In Nb2 and Baf3supporting
confidence: 94%
“…1 and 2). These data are consistent with our earlier study in which PL-I showed higher proliferating activity than PRL (4).…”
Section: Induction Of Pal31 Expression In Nb2 and Baf3supporting
confidence: 94%
“…It is assumed that PLs activate signal transduction pathways downstream of the PRL-R similar to those activated by PRL. Beyond the abilities of members of the PL-I subfamily to stimulate the Jak-Signal Transducer and Activator of Transcription (STAT) pathway in Nb2 lymphoma cells [95,96] and cultured luteinized granulosa cells [80], information on intracellular signaling pathways triggered by classical members of the placental PRL family is lacking. It seems likely that at least some aspects of PRL signaling are mimicked by PLs; however, whether these uteroplacental ligands reproduce the full spectrum of PRL action or elicit unique responses is unknown.…”
Section: Reviewmentioning
confidence: 99%
“…Western blotting of PAL31 and PL-I was performed using standard protocols (20). Cell lysates of proliferating and differentiated Rcho-1 cells were prepared by adding lysis buffer (10 mM phosphate buffer, pH 7.0, containing 300 mM NaCl, 0.1% SDS, 1% Nonidet P-40, 0.5% sodium deoxycholate, 1 mM NaF and protease inhibitors), and incubating for 20 min on ice.…”
Section: Northern Blot Analysesmentioning
confidence: 99%